Retinal and optic nerve relapse in retinoblastoma secondary to epiretinal and epipapillary vitreous seeds implantation documented by optical coherence tomography. (2nd November 2022) - Stathopoulos, Christina; Tripathy, Devjyoti; Moulin, Alexandre; Beck-Popovic, Maja; Munier, Francis L.
ABSTRACT: Background: Retinal retinoblastoma growth phenotypes can be endophytic, exophytic, diffuse infiltrating or anterior diffuse. Herein, we describe a novel tumor growth pattern in two patients. Material and Methods: Imaging with spectral-domain optical coherence tomography (SD-OCT) Results: Both cases were diagnosed with unilateral group D retinoblastoma treated with first-line or bridge intra-arterial chemotherapy (IAC). Case 1 had a new intravitreal/epiretinal relapse 3 months after brachytherapy and intravitreal chemotherapy. SD-OCT showed a disruption of the inner limiting membrane (INL) underneath a parapapillary epiretinal seed. The intravitreal/epiretinal disease completely regressed with intravitreal melphalan. Three months later, an isolated intraretinal growth was documented on SD-OCT at the site of previously INL disruption, which was treated by thermotherapy. He remained disease-free at 1-year follow-up with 0.6 visual acuity. Case 2 was seen 2 months after treatment interruption due to the COVID-19 pandemic. Fundus examination showed a massive intravitreal/epipapillary invasion completely obscuring the papilla. Salvage treatment of this seeing eye consisted of combined intra-arterial and intravitreal melphalan and topotecan injections. An infraclinical papillary regrowth 4 months later was treated with additional IAC. Six months later, enucleation was performed due to an infraclinical papillary relapse with suspicion of intralaminar invasion. Histopathology showed retrolaminar optic nerve invasion with tumor-free surgical section. The child received four cycles of adjuvant chemotherapy and remained disease-free at 1-year follow-up. Conclusion: Epiretinal/epipapillary vitreous seeding can be the source of a secondary intraretinal/optic nerve head relapse. SD-OCT is instrumental to follow such cases. Enucleation remains the safest option if secondary optic nerve invasion is suspected.